Analisis faktor penyebab cost overrun dan time overrun yang mempengaruhi kinerja keuangan proyek PLTU Lombok FTP-2 (2x50 MW) dengan pendekatan Partial Least Square Structural Equation Modeling (PLS-SEM) - Sunarko Sunarko*; Machsus Machsus; Muhammad Ainul Fahmi (Universitas Syiah Kuala, 2023)
Power plant projects have an important role in fulfilling the electricity needs of society. However, like other construction projects, power plant projects often experience problems such as cost overrun and time overrun, which can cause financial losses and project delays. Cost overrun is the difference between the actual project cost and the planned cost, while time overrun is the delay in works that exceed the specified contract date, or the date agreed by the parties to the project. This study aims to analyze the factors that influence cost overrun and time overrun in the CFSPP Lombok FTP-2 project (2x50 MW) using Partial Least Squares (PLS) Structural Equation Modeling (SEM). This research was conducted by studying literature related to cost overrun, time overrun, and its causing factors in construction projects. Data was collected through questionnaires and was online distributed to 78 respondents contractor involved in the project. The examination of the inner and outer models is used to analyze the data obtained from research utilizing the Smart PLS 4.0 application. Based on the data analysis, it is revealed that there are nine research hypotheses, with five hypotheses being accepted and four hypotheses being rejected. The factors that contribute to time overrun and cost overrun, according to the accepted hypotheses, include Contractor's Site Management Factors, Design and Documentation Factors, Information and Communication Factors, Project Management and Contract Administration Factors, and Time overrun. Based on these findings, recommendations for management are proposed, which include a contractor project management takeover scheme and the addition of new members to the project consortium